Contribution to the hyaliodine fauna (Miridae: Deraeocorinae: Hyaliodini) of New Caledonia with a description of two new species and a checklist of New Caledonian plant bugs - Gierlasiński, Grzegorz; Taszakowski, Artur (Zootaxa, 2024)
Two new species of the Montagneria Akingbohungbe, 1978—M. barbarae sp. nov. and M. nataliae sp. nov.—are diagnosed and described. Photographic images of habitus and genital structures, as well as scanning electron micrographs of the selected structures of both species are provided. The gland openings located on the thorax are figured and discussed. New records of three hyaliodine species, Femurocoris spinosus Carvalho, 1977, Montagneria cuneatus (Distant, 1920), and M. nigroscutellatum (Distant, 1920) in New Caledonia are also presented. Moreover, a checklist of the Miridae species of New Caledonia is given.